Prosedur Pelayanan Perpanjangan IPTM Pada Sudin Pertamanan Dan Hutan Kota TPU Tegal Alur Unit Kristen Jakarta Barat - Purnama Sari; Syukron Sazly (Jurnal Administrasi Bisnis, 2021)
Public Cemetery is a public facility that is social in nature and already exists in the scope of services and public services in the Special Capital Region of Jakarta. A public cemetery is a place with large tracts of land intended for people who have died and become the final resting place. The public cemetery has been neatly arranged with a function as a Green Open Space filled with green trees, grass on the body of a tomb that looks beautiful. Tegal Alur Public Cemetery with a land area of approximately ± 94,810 m2 with Christian funeral service units under the auspices of the funeral section of suku dinas pertamanan dan hutan kota, West Jakarta administration city, providing administrative services to the wider community, regarding funerals, funeral maintenance, and also as one of the regional retribution tax revenues.  This study aims to find out how, obtacles and solutions in Administrative Procedures for the Extension of IPTM Services at Suku Dinas Pertamanan dan Hutan Kota, TPU Tegal Alur Unit Kristen Jakarta Barat. The method used is a study, observation and interviews were also conducted with several speakers at Suku Dinas Pertamanan dan Hutan Kota, Tpu Tegal Alur Unit Kristen, located on Jl. Benda Raya No.17 RT.008 RW.002, Kelurahan Tegal Alur, Kalideres District, West Jakarta City, Special Capital Region of Jakarta 11820. The results of the study at the Administrative Procedures for the Extension of IPTM Services at Suku Dinas Pertamanan dan Hutan Kota, TPU Tegal Alur Unit Kristen Jakarta Barat, it can be said to be good enough with an easy-to-understand stage, but there are some obstacles that occur so that it can hamper the smooth implementation of the IPTM Extension Service.   Key Words:  Public Cemetery (TPU), Administration, Services, Public Services